The translation process and the implementation of its methods through the employment of information and communication technologies - Aldana Rodríguez, Jorge Luis; Galán Menjívar, Estefany Lisseth; Lara Manzano, Adriana Lisbeth (2024)
Is it necessary to stick to a process in order to develop a flawless translation? Throughout civilization history there has been a necessity of communicating ideas among different languages. At the beginning, the people manage to understand each other, but later they notice that is not enough to communicate, it is a must that people understand the whole message, and that it would be semantically and grammatically correct. As students of the major modern languages but having the honor to deeply study about translation we certainly believe that translation makes our current world an educated world. Nonetheless, to have an efficient translation practice, there should always exist a path, a structure to follow, and it belongs to every translator. The main techniques that are always applied in the texts presented are reading, research of unknown vocabulary, first time translation, opinion of different colleagues, transcription and proofreading. All of them help step by step to get a comprehensible, natural, and impeccable text. By checking this report, you will notice how our process is applied in every translation included in the portfolio, and how every step aims to prepare the best version to the target language of any text.